2021
DOI: 10.3389/fneur.2021.620367
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perturbation-Based Balance Training and Conventional Intensive Balance Training on Reactive Stepping Ability in Individuals With Incomplete Spinal Cord Injury or Disease: A Randomized Clinical Trial

Abstract: Introduction: Impaired balance leads to falls in individuals with motor incomplete spinal cord injury or disease (iSCI/D). Reactive stepping is a strategy used to prevent falls and Perturbation-based Balance Training (PBT) can improve this ability.Objective: The objective of this study was to determine if PBT results in greater improvements in reactive stepping ability than frequency-matched Conventional Intensive Balance Training (CIBT) in adults with iSCI/D.Design: Randomized clinical trial.Setting: Tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Second, providing a safe environment in which to experience losses of balance when standing, walking, wheeling and/or transferring may provide opportunities for experiential learning. While reactive balance training, which provides repetitive exposure to falls, has been studied in the chronic, ambulatory SCI/D population to date [ 46 ], there may be value in investigating its feasibility and efficacy in the subacute population and modifying the training to accommodate wheelchair users.…”
Section: Discussionmentioning
confidence: 99%
“…Second, providing a safe environment in which to experience losses of balance when standing, walking, wheeling and/or transferring may provide opportunities for experiential learning. While reactive balance training, which provides repetitive exposure to falls, has been studied in the chronic, ambulatory SCI/D population to date [ 46 ], there may be value in investigating its feasibility and efficacy in the subacute population and modifying the training to accommodate wheelchair users.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in studies included in this review were community-living older adults; 9, 31, 33-35, 40, 45, 47, 48, 51 adults with Parkinson’s disease, 27, 29, 32, 37, 38, 41, 42 stroke, 8, 30, 39, 44, 46 cerebral palsy, 36 and spinal cord injury; 49 and long-term care residents. 28, 43 All studies had RBT as either a sole or a significant component of the experimental intervention.…”
Section: Resultsmentioning
confidence: 99%
“…33, 35, 45 The frequency of RBT ranged from one training session total 33, 35, 48 to 3 times per week. 9, 27-32, 34, 41, 43, 47, 49 The duration of RBT training ranged from 15 minutes 33 to 1.5 hours 36 per session; most studies (19/25) conducted RBT for 30 to 60 minutes per session.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants also demonstrated an increased center of pressure excursion in all directions when leaning in a standing position [57]. Gauthier et al (2020) recently demonstrated the feasibility of incorporating FES into perturbation-based balance training, which involves repetitively exposing individuals with SCI to external perturbations to help retrain reactive postural control [64][65][66]. Surface electrodes were placed on the common fibular nerve bilaterally to elicit the flexor withdrawal response.…”
Section: Retraining Standing Postural Control With Fesmentioning
confidence: 99%